The naturalistic teaching process as an inclusive practice: Preschool teachers' perspectives - Düriye Merve Tuna; Ibrahim Halil Diken (Journal of Childhood, Education & Society)
According to the Ministry of National Education, 2013, children with diverse needs have the right to receive their education in environments designed to meet their needs and allow them to interact with their peers. Instructional programs that can meet all children’s needs are one of the suggested programs during the implementation of inclusive programs. The Naturalistic Teaching Process is a recommended method in this context. The Naturalistic Teaching Process is a natural instructional process that allows children to acquire and reinforce new skills. This study aims to define the perspectives of preschool teachers who have children with diverse needs in their classrooms on the Naturalistic Teaching Process. Semi-structured interviews collected the data. Fifteen preschool teachers participated in this study. The data analysis employed an inductive approach based on content analysis. The study findings indicate that preschool teachers tend to follow a child's lead when setting educational objectives for children with diverse needs and developing an individualized educational program. Additionally, the study defines preschool teachers' abilities as inadequate for collaboration with families and specialists. Preschool teachers partially use the strategies and techniques, environmental arrangements, and prompts used in the Naturalistic Teaching Process, but they do not apply them systematically, indicating a need for teacher training in these areas.